Impact of COVID-19 on livestock exports from Somalia and the Horn of Africa - Banerjee, Rupsha R.; Cullis, Adrian; Flintan, Fiona E.; Wiggins, Steve (Practical Action Publishing, 2021)
Somalia has a significant place in the livestock sector in the Horn of Africa; livestock trade and export is one of the key economic contributors. Most of the livestock trade happens with the Middle East, the Kingdom of Saudi Arabia being one of its biggest importers. The COVID-19 pandemic has led to both massive loss of life and huge economic losses as the result of measures to contain the virus. In June 2020, the Kingdom of Saudi Arabia took the decision to restrict the number of pilgrims for the annual Hajj. Impacts resulted in a decline in income from the seasonal Hajj of 80 per cent, though domestically prices of livestock remained stable and local markets were used for livestock sales. This paper, besides highlighting the effects, provides recommendations which could inform strategic planning, humanitarian aid, and resilience building for the livestock value chain in Somalia and the Horn of Africa